Obstructive Sleep Apnea Is Associated With Low Testosterone Levels in Severely Obese Men - Tančić-Gajić, Milina; Vukčević, Miodrag; Ivović, Miomira; Marina, Ljiljana V.; Arizanović, Zorana; Soldatović, Ivan; Stojanović, Miloš; Đogo, Aleksandar; Kendereški, Aleksandra; Vujović, Svetlana (Frontiers in Endocrinology, 2021)
Background: Disrupted sleep affects cardio-metabolic and reproductive health. Obstructive sleep apnea syndrome represents a major complication of obesity and has been associated with gonadal axis activity changes and lower serum testosterone concentration in men. However, there is no consistent opinion on the effect of obstructive sleep apnea on testosterone levels in men. Objective: The aim of this study was to determine the influence of obstructive sleep apnea on total and free testosterone levels in severely obese men. Materials and methods: The study included 104 severely obese (Body Mass Index (BMI) ≥ 35 kg/m2) men, aged 20 to 60, who underwent anthropometric, blood pressure, fasting plasma glucose, lipid profile, and sex hormone measurements. All participants were subjected to polysomnography. According to apnea-hypopnea index (AHI) patients were divided into 3 groups: <15 (n = 20), 15 - 29.9 (n = 17) and ≥ 30 (n = 67). Results: There was a significant difference between AHI groups in age (29.1 ± 7.2, 43.2 ± 13.2, 45.2 ± 10.2 years; p < 0.001), BMI (42.8 ± 5.9, 43.2 ± 5.9, 47.1 ± 7.8 kg/m2; p = 0.023), the prevalence of metabolic syndrome (MetS) (55%, 82.4%, 83.6%, p = 0.017), continuous metabolic syndrome score (siMS) (4.01 ± 1.21, 3.42±0.80, 3.94±1.81, 4.20 ± 1.07; p = 0.038), total testosterone (TT) (16.6 ± 6.1, 15.2 ± 5.3, 11.3 ± 4.44 nmol/l; p < 0.001) and free testosterone (FT) levels (440.4 ± 160.8, 389.6 ± 162.5, 294.5 ± 107.0 pmol/l; p < 0.001). TT level was in a significant negative correlation with AHI, oxygen desaturation index (ODI), BMI, MetS and siMS. Also, FT was in a significant negative correlation with AHI, ODI, BMI, age, MetS and siMS. The multiple regression analysis revealed that both AHI and ODI were in significant correlation with TT and FT after adjustment for age, BMI, siMS score and MetS components. Conclusion: Obstructive sleep apnea is associated with low TT and FT levels in severely obese men.